Autophagy proteins are not universally required for phagosome maturation. Issue 9 (1st September 2016) - Cemma, Marija; Grinstein, Sergio; Brumell, John H.
ABSTRACT: Phagocytosis plays a central role in immunity and tissue homeostasis. After internalization of cargo into single-membrane phagosomes, these compartments undergo a maturation sequences that terminates in lysosome fusion and cargo degradation. Components of the autophagy pathway have recently been linked to phagosome maturation in a process called LC3-associated phagocytosis (LAP). In this process, autophagy machinery is thought to conjugate LC3 directly onto the phagosomal membrane to promote lysosome fusion. However, a recent study has suggested that ATG proteins may in fact impair phagosome maturation to promote antigen presentation. Here, we examined the impact of ATG proteins on phagosome maturation in murine cells using FCGR2A/FcγR-dependent phagocytosis as a model. We show that phagosome maturation is not affected in Atg5 -deficient mouse embryonic fibroblasts, or in Atg5 - or Atg7 -deficient bone marrow-derived macrophages using standard assays of phagosome maturation. We propose that ATG proteins may be required for phagosome maturation under some conditions, but are not universally required for this process.